Coherent Perfect Absorption in a Transparent Polymer Film on a Transparent Substrate Utilizing Total Internal Reflection by Grazing Incidence - Mayu Hasegawa; Junpei Oi; Kyohei Yamashita; Keisuke Seto; Takayoshi Kobayashi; Eiji Tokunaga (Applied Sciences, 2022)
A simple scheme for single-channel coherent perfect absorption (CPA) of transparent materials is proposed and experimentally realized using total internal reflection by grazing incidence, with a single dielectric layer sandwiched by semi-infinite dielectric layers. In a 1.48-µm thick polyvinylpyrrolidone (PVP) film, dip-coated on a MgF2 substrate both transparent in the visible, reflectance dips due to nearly 90% absorption by single-channel CPA were observed in the wavelength range of 370–800 nm, with white light from a Xe lamp incident on the side face of the substrate and extracted from the other side through multiple reflections in the PVP layer. This is a simple and inexpensive CPA scheme, and it is expected to have various applications by changing the substrate/polymer material or dispersing molecules in the polymer film. This paper also provides a design guideline for grazing-incidence waveguide-mode sensors using transparent dielectric materials.